Molecular and histopathological characterization of Ascaridia galli and Eimeria tenella co-infection in Numida meleagris - Attia, Marwa M.; Mahmoud, Mahmoud A.; Abdelsalam, Mohamed; Almutairi, Layla A.; Alqahtani, Mohammed A.; Areshi, Sultan Mohammed; El-Saadony, Mohamed T.; El-Tarabily, Khaled A.; Salem, Heba M. (Frontiers in Veterinary Science, 2025)
IntroductionThe helmeted guineafowl is a ground-dwelling bird native to Africa, easily recognized by its bald, bluish-gray head and the distinctive horn-like casque (helmet) on top of its head. Parasitic coinfection with Ascaridia worms and Eimeria in chickens poses a significant health challenge, as both parasites damage the intestinal tract and impair nutrient absorption. Ascaridia galli competes for nutrients and causes mechanical irritation, while Eimeria tenella induces mucosal injury and inflammation. Their combined effect leads to severe enteritis, reduced growth performance, poor feed conversion, and increased susceptibility to secondary infections. This synergistic impact exacerbates economic losses in poultry production and highlights the importance of integrated parasite control strategies.MethodsThis study investigated the cause of mortality in helmeted guineafowl on a private farm. Clinical examination, necropsy, parasitological analysis, molecular characterization, and histopathological examination were conducted.ResultsPreliminary findings indicated a mixed gastrointestinal parasitic infection, with A. galli and E. tenella identified as the causative agents of co-infection. Molecular analysis targeting the ITS rDNA and COX1 regions of A. galli and the ITS and 18S rDNA regions of E. tenella confirmed their identities and revealed genetic diversity among the isolates. Phylogenetic analysis clustered the isolates within well-supported clades of their respective species. Clinical signs included depression and sporadic hemorrhagic droppings, while postmortem lesions varied, featuring enteritis, hemorrhagic typhlitis, splenic necrosis, and hepatic lesions. Histopathological examination revealed severe intestinal damage, including hemorrhage, epithelial desquamation, and the presence of multiple parasite developmental stages. The co-infection led to a 10% mortality rate.DiscussionThe current study offers insights into the impact of A. galli and E. tenella co-infection in helmeted guineafowl, underscoring the importance of molecular surveillance in monitoring poultry parasite populations. Additional research is recommended to establish routine parasitological monitoring, implement targeted deworming initiatives, enhance sanitation, and enforce biosecurity protocols to reduce parasite load and prevent epidemics.